2017
DOI: 10.1002/jcp.26124
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐146a protects small intestine against ischemia/reperfusion injury by down‐regulating TLR4/TRAF6/NF‐κB pathway

Abstract: Previous studies reported that miR-146a was involved in small intestine ischemia-reperfusion (I/R) injury, but the mechanism is largely vague. Here, we aimed to identify the change of miR-146a in patients with mesenteric ischemia and explore the potential regulatory mechanism of miR-146a in intestine epithelial cells survival under ischemia and I/R injury. The plasma of 20 patients with mesenteric ischemia and 25 controls was collected to examine the miR-146a expression by qPCR. Rat intestinal epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 32 publications
3
42
1
Order By: Relevance
“…MicroRNAs (miRNAs) are important endogenous regulators leading to RNA degradation and/or inhibition of protein synthesis (He et al, ; Y. Hu et al, ; Z. Liu et al, ). Recent studies have shown that some miRNAs including miR‐378, miR‐351‐5P, and miR‐665‐3p play important roles in regulating II/R injury (Y. Hu et al, ; Z. Li et al, ; Y. Li, Wen, et al, ; Y. Li, Xu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are important endogenous regulators leading to RNA degradation and/or inhibition of protein synthesis (He et al, ; Y. Hu et al, ; Z. Liu et al, ). Recent studies have shown that some miRNAs including miR‐378, miR‐351‐5P, and miR‐665‐3p play important roles in regulating II/R injury (Y. Hu et al, ; Z. Li et al, ; Y. Li, Wen, et al, ; Y. Li, Xu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are important endogenous regulators leading to RNA degradation and/or inhibition of protein synthesis (He et al, 2018;Y. Hu et al, 2018;Z.…”
Section: Introductionmentioning
confidence: 99%
“…40 MicroRNA-146a was also suppressed 15-fold in the LCHS/CS group compared with LCHS/CSþBB and naïve rodents. He and colleagues 41 found decreased expression of miR-146a in patients with small intestine ischemia and ischemia reperfusion injury, and determined that improved intestine epithelial cell survival occurs with inhibition of Toll-like receptor 4 and tumor necrosis factor receptor-associated factor-6, leading to decreased nuclear factor kappa light chain enhancer of activated B cells, which has been shown to play a role in early erythroid proliferation and suppression of erythroid specific genes. 42 These miR findings correlate with our previous studies demonstrating significant erythroid growth suppression after LCHS/CS and improvement in inflammation and erythropoiesis with the use of propranolol after LCHS/CS.…”
Section: Discussionmentioning
confidence: 99%
“…TnF receptor-associated factor (TraF) is an important linker molecule in the TnF superfamily; TRAF6 is involved in inflammation and immune responses by mediating inflammatory and apoptotic signaling pathways (15). in addition, TraF may serve a key role by activating the nF-κB signaling pathway (16)(17)(18)(19)(20)(21)(22)(23). a previous study reported that BaFF activates B cells through the nF-κB signaling pathway to secrete excess iga1, which leads to iga nephropathy-like alterations in mouse kidneys (14).…”
Section: Introductionmentioning
confidence: 98%